Morphological characterization of Calotropis procera (Aiton) W.T. Aiton, a neglected medicinal plant - Ali Khadivi; Farhad Mirheidari; Yazgan Tunç; Abdolvahid Saeidifar; Younes Moradi; Vali Rabiei; Farhang Razavi (PLoS ONE, 2026)
Calotropis procera (Aiton) W.T. Aiton, a medicinally significant but understudied species, exhibits remarkable adaptability to arid environments. Despite its ecological and pharmacological value, the species remains poorly characterized morphologically. This study evaluated the morphological diversity of 50 C. procera accessions from Sistan-va-Baluchestan province, Iran, using multivariate statistical approaches to identify key phenotypic variations and their potential applications. Significant morphological variability was observed among the accessions, with 37 out of 53 traits exhibiting coefficients of variation greater than 20%. Fruit-related traits, such as fruit length and weight, exhibited the highest variability, with the first principal component (PC1) explaining 17.45% of the total variance. Leaf characteristics, including color and pubescence, were dominant in the second principal component (PC2), accounting for 14.53% of the variance. Multiple regression analysis revealed a strong positive correlation between fruit weight and fruit length ( β = 0.73, p ≤ 0.00). A trade-off was observed between flower number and fruit weight ( β = −0.32, p ≤ 0.00). Heat map analysis grouped the accessions into four distinct clusters, with ‘Roodan-10’ and ‘Bahoukalat-1’ standing out for their superior fruit and floral traits, respectively. Notably, accessions such as ‘Dargas-10’ (100-seed weight: 2.40 g), ‘Rask-8’ (seed hair length: 30.19 mm), and ‘Pishin-8,’ distinguished by its exceptional leaf dimensions (mature leaf width: 139.20 mm), were identified as potential candidates for breeding. The remarkable leaf size of ‘Pishin-8’ suggests a high level of photosynthetic efficiency, which could enhance biomass production, further contributing to the ecological and agronomic value of this accession due to its exceptional seed characteristics. This study provides the first comprehensive morphological evaluation of C. procera , highlighting its high phenotypic diversity and adaptive traits. The findings underscore the species’ potential for medicinal and ecological applications, with specific accessions offering valuable genetic resources for conservation and breeding programs. Future research integrating molecular analyses is recommended to elucidate the genetic basis of observed variations.